Does Market-Based Environmental Regulation Improve the Residents' Health: Quasi-Natural Experiment Based on DID - Bingnan Guo PhD; Weizhe Feng MD; Ji Lin PhD (SAGE Publishing, 2024)
Improving the residents' health is an important strategy for addressing the declining population dividend in China under the new development paradigm. Based on the panel data of 290 prefecture-level cities in China from 2010 to 2021, this paper uses environmental tax as a quasi-natural experiment, and adopts a DID model to explore the impact of market-based environmental regulation on the residents' health. The results show that the implementation of environmental tax can significantly reduce the population mortality rate, indicating an enhancement in residents' health outcomes. Mechanism analysis shows that environmental tax mainly relies on air quality to improve the residents' health. Also, the heath effect of environmental tax will be effective with the increase of income, and it's stronger in administrative border areas. Heterogeneity analysis shows that the effect of environmental tax on residents' health in western regions and resource-based cities is significantly stronger than those in central and eastern regions and non-resource-based cities. This paper provides new evidence for a comprehensive understanding of the impact of market-based environmental regulations on residents' well-being, offering insights for the implementation of green development strategies.